Development of the SF-6Dv2 health utility survey: comprehensibility and patient preference - Lynne Broderick; Jakob B. Bjorner; Miranda Lauher-Charest; Michelle K. White; Mark Kosinski; Brendan Mulhern; John Brazier (SpringerOpen, 2022)
Abstract Background The SF-6Dv2 classification system assesses health states in six domains-physical functioning, role function, bodily pain, vitality, social functioning, and mental health. Scores have previously been derived from the SF-36v2® Health Survey. We aimed to develop a six-item stand-alone SF-6Dv2 Health Utility Survey (SF-6Dv2 HUS) and evaluate its comprehensibility. Methods Two forms of a stand-alone SF-6Dv2 HUS were developed for evaluation. Form A had 6 questions with 5-6 response choices, while Form B used 6 headings and 5-6 statements describing the health levels within each domain. The two forms were evaluated by 40 participants, recruited from the general population. Participants were randomized to debrief one form of the stand-alone SF-6Dv2 HUS during a 75-min interview, using think-aloud techniques followed by an interviewer-led detailed review. Participants then reviewed the other form of SF-6Dv2 and determined which they preferred. Any issues or confusion with items was recorded, as was as overall preference. Data were analyzed using Microsoft Excel and NVivo Software (v12). Results Participants were able to easily complete both forms. Participant feedback supported the comprehensibility of the SF-6Dv2 HUS. When comparing forms, 25/40 participants preferred Form A, finding it clearer and easier to answer when presented in question/response format. The numbered questions and underlining of key words in Form A fostered quick and easy comprehension and completion of the survey. However, despite an overall preference for Form A, almost half of participants (n = 19) preferred the physical functioning item in Form B, with more descriptive response choices. Conclusion The results support using Form A, with modifications to the physical functioning item, as the stand-alone SF-6Dv2 HUS. The stand-alone SF-6Dv2 HUS is brief, easy to administer, and comprehensible to the general population.